Dyadic associations of physical activity intensity with fertility-related quality of life in infertile couples: an APIM analysis - Fei Jiang; Zhengmei Liao; Yanan Chen; Qiufeng Gu; Guiying Luo; Qianhua Xu; Jieyu Wang; Danni Wang (Frontiers in Public Health, 2026)
Objective Infertility is a condition that intrinsically affects both members of a couple. However, the dyadic associations between physical activity intensity and fertility-related quality of life (FertiQoL) remains insufficiently explored. This study aimed to examine dyadic associations between physical activity intensity and FertiQoL among infertile couples undergoing assisted reproductive technology (ART) treatment. Methods This cross-sectional study included 364 infertile couples receiving ovulation induction treatment at a reproductive medicine center. Physical activity levels and FertiQoL were assessed using validated questionnaires. Multivariable linear regression was used to examine overall associations between physical activity and FertiQoL domains. The Actor–Partner Interdependence Model (APIM) was applied to estimate actor associations (individual physical activity with own FertiQoL) and partner associations (individual physical activity with spouse’s FertiQoL). Results Women reported significantly lower physical activity levels and FertiQoL scores compared to men (all p < 0.05). Overall, higher total physical activity (TPA) and most intensity levels were positively associated with multiple FertiQoL domains. The adjusted APIM analysis demonstrated a significant actor association among husbands, whereby higher light physical activity (LPA) was associated with better own FertiQoL ( β = 0.205, 95% CI: 0.076 to 0.335, p = 0.002). Notably, distinct intensity-dependent partner effects were observed: wives’ moderate physical activity (MPA) was positively associated with husbands’ FertiQoL ( β = 0.150, 95% CI: 0.024 to 0.277, p = 0.021), whereas wives’ vigorous physical activity (VPA) was negatively associated with husbands’ FertiQoL ( β = −0.184, 95% CI: −0.307 to −0.061, p = 0.004). Conclusion Physical activity is significantly associated with quality of life among infertile couples in an intensity-dependent manner. More importantly, physical activity demonstrates dyadic interdependence, with wives’ physical activity exerting intensity-specific effects on husbands’ FertiQoL. These findings highlight the importance of considering couple-level lifestyle behaviors in infertility care and suggest that dyadic lifestyle approaches warrant further evaluation as potential supportive strategies during ART treatment.